2019
DOI: 10.3400/avd.oa.19-00007
|View full text |Cite
|
Sign up to set email alerts
|

STAT3 Activation Correlates with Adventitial Neutrophil Infiltration in Human Aortic Dissection

Abstract: Objective : Aortic dissection (AD) is a fatal disease that is caused by the rapid destruction of the aortic wall. Although recent studies in animal models indicate an important relationship between inflammation and tissue destruction, activation status of inflammatory signaling and its relation to the inflammatory cell infiltration are poorly characterized in human AD. Materials and Methods : We examined the activation of inflammatory signaling molecules NFκB and STAT3, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 22 publications
4
18
0
Order By: Relevance
“…Previous studies show that neutrophil infiltration is predominant in the acute phase of human TAD [5][6][7] . In a murine model of thoracic aortic dissection, neutrophils were shown to be an important mediator in the initiation of TAD, as the antibody-mediated depletion of neutrophils attenuated TAD formation 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies show that neutrophil infiltration is predominant in the acute phase of human TAD [5][6][7] . In a murine model of thoracic aortic dissection, neutrophils were shown to be an important mediator in the initiation of TAD, as the antibody-mediated depletion of neutrophils attenuated TAD formation 7 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the direct cellular and molecular mechanism that is involved in the onset of TAD has not been fully elucidated. Several studies reported that neutrophil infiltration is predominant in the acute phase of human TAD [5][6][7] . CD44 is a widely distributed cell surface marker and cell adhesion molecule that serves as a principle receptor for extracellular matrix components such as hyaluronan 8,9 , Under inflammatory conditions, CD44 is upregulated on inflammatory cells including neutrophils, monocytes, and lymphocytes 10 .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In an animal model, inflammation of the adventitia characterized by neutrophil recruitment was shown to promote tissue damage, leading to aortic dilation and rupture [8]. Moreover, a recent study of surgically resected aortic specimens revealed association between activation of STAT 3 in adventitial tissue and neutrophil infiltration [9].…”
Section: Introductionmentioning
confidence: 99%
“…Studies in human AD samples and animal AD models indicate that inflammatory response plays a central role in the pathogenesis of AD [3,4]. We also reported the involvement of inflammatory response in mouse models [5][6][7] and in human AD tissue [8]. Although these studies demonstrated the importance of inflammation, it remains elusive how inflammatory response is initiated or whether and how it is related to SMC cytoskeleton.…”
Section: Introductionmentioning
confidence: 79%